Rozwiąż układ równań metodą podstawiania.
a) { y/3 - x/4 +1/3=1/2 i y/4 - 5/8= - x/3 - 1/2
b) { 2x-3(x+y) +14= y -2 i 2(x-y) +3y+3= 2y -1
c) x- y/2 - 1= -1/6 - x-2y/3 i x/3 - y/2 = 5/6
d) 4(2a-b)/3 +b/2 = 1/2 (a-b) +8 +2(a+b)/3 i -1+ 3-b/4= a+1/3
e) a(a-b) +2(b-2)(a+3) = (a+b)(a-1) i a/3 - b/2=1/3
f) (x-1)do kwadratu +y(y-2x)= (x-y) do kwadratu +5 i
y(1-x)-1= x(1-y)


Z góry dzięki;*:)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T19:59:24+01:00
A) y/3-x/4+1/3=1/2 /*12 i y/4-5/8=-x/3-1/2 /*24
4y-3x+4=6 i 6y-15=-8x-12
-3x=6-4y-4 i 6y=-8x-12+15
-3x=-4y+2 /:(-3) i 6y=-8x+3
x=4/3y-2/3 i 6y=-8*(4/3y-2/3)+3
x=4/3y-2/3 i 6y=-32/3y+16/3+3
x=4/3y-2/3 i 18/3y+32/3y=25/3
x=4/3y-2/3 i 50/3y=25/3 /*3/50
x=4/3y-2/3 i y=1/2
x=4/3*1/2-2/3 i y=1/2
x=0 i y=1/2
b)2x-3(x+y)+14=y-2 i 2(x-y)+3y+3=2y-1
2x-3x-3y+14=y-2 i 2x-2y+3y+3=2y-1
-x=y-2+3y-14 i -2y+3y-2y=-1-2x-3
-x=4y-16 /*(-1) i -y=-4-2x /*(-1)
x=-4y+16 i y=4+2x
x=-4y+16 i y=4+2*(-4y+16)
x=-4y+16 i y=4-8y+32
x=-4y+16 i y+8y=36
x=-4y+16 i 9y=36/:9
x=-4y+16 i y=4
x=-4*4+16 i y=4
x=0 i y=4